Conceptualising the education and care workforce from the perspective of children and young people - Cartmel, Jennifer; Irvine, Susan; Harrison, Linda; Barblett, Lennie; Bobongie-Harris, Francis; Lavina, Leanne; Hadley, Fay (Frontiers in Education, 2023)
Children and young people are significant stakeholders within education and care settings. Their views can be invaluable in thinking about what matters to conceptualising, assessing and improving quality in Early Childhood Education and Care (ECEC) and Outside School Hours Care (OSHC) settings. As stakeholders, children’s views are rarely listened to by Australian policy makers to assess what constitutes quality and how the quality can be improved. In the process of updating two nationally approved Australian Learning Frameworks (ALFs): Belonging, Being and Becoming: The Early Years Learning Framework for Australia and My Time Our Place: Framework for School Age Care in Australia, children and young people’s responses provided meaningful insights into their perceptions of the practices of the educators. The children and young people’s perspectives were gathered in a combination of research methodologies of talking circles, dialogic drawing, and visual elicitation. Their responses about experiences in Early Childhood Education and Care (ECEC) and Outside School Hours Care (OSHC) contexts were analysed to provide a deeper understanding about the characteristics of their experiences in the settings. The research process delivered information about children’s perspectives about pedagogical principles and practices that describe the Australian children’s education and care workforce and environments. The process of gathering the children’s perspectives is not without limitations, however the information is invaluable in considering the assessment and improvement of quality in children’s services.